Citizen leadership deepening democratic accountability in India, Brazil, and South Africa - Jha, Vikas; Vaishnava, Bhavita; Bandyopadhyay, Kaustuv Kanti; Academic Foundation (New Delhi, India); Society for Participatory Research in Asia. (New Delhi Academic Foundation, 2011)
Contributed articles.
Includes bibliographical references.
Keywords: Democracy -- India -- Citizen participation; Democracy -- Brazil -- Citizen participation; Democracy -- South Africa -- Citizen participation